1987
DOI: 10.1161/01.cir.75.5.906
|View full text |Cite
|
Sign up to set email alerts
|

Coronary wedge pressure in relation to spontaneously visible and recruitable collaterals.

Abstract: Coronary angiography demonstrates only collateral arteries that are already in use (spontaneously visible collaterals). Percutaneous transluminal coronary angioplasty (PTCA) provides an opportunity to uncover collaterals ready to become functional in case of occlusion of the recipient artery (recruitable collaterals). spontaneously visible on a routine coronary angiogram and with that of recruitable collaterals. MethodsDefinitions. The coronary wedge pressure was defined as the mean distal coronary pressure me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
2

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(36 citation statements)
references
References 21 publications
(2 reference statements)
3
31
0
2
Order By: Relevance
“…Current angiographic equipment reveals only vessels with luminal diameters of at least 100 gm. Whether 22 We have shown that the coronary wedge pressure not only reflects already visible collaterals but also recruitable collaterals not visible on diagnostic angiograms.22 Furthermore, an increased restenosis rate was reported to be associated with both angiographically well-developed collateral2' and a high coronary wedge pressure. 29 In the present study, we have considered the distal coronary pressure determined during percutaneous balloon revascularization of totally occluded coronary arteries as a functional indicator of collateral circulation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Current angiographic equipment reveals only vessels with luminal diameters of at least 100 gm. Whether 22 We have shown that the coronary wedge pressure not only reflects already visible collaterals but also recruitable collaterals not visible on diagnostic angiograms.22 Furthermore, an increased restenosis rate was reported to be associated with both angiographically well-developed collateral2' and a high coronary wedge pressure. 29 In the present study, we have considered the distal coronary pressure determined during percutaneous balloon revascularization of totally occluded coronary arteries as a functional indicator of collateral circulation.…”
Section: Discussionmentioning
confidence: 90%
“…The hemodynamics of coronary collaterals have been studied directly in humans during aortocoronary bypass surgery,17 and, more recently, the pressure distally to coronary lesions was measured during percutaneous angioplasty18-22 and the relation of the coronary wedge pressure (pressure in the distal part of the occluded artery) to spontaneously visible and recruitable collaterals has been established. 22 To evaluate the protective role of the coronary collateral circulation, we studied the relation between the mean coronary wedge pressure measured during percutaneous transluminal coronary angioplasty and the left ventricular function in patients with occlusion of a major coronary vessel.…”
mentioning
confidence: 99%
“…19 Furthermore, even though the overlap between quantitative measures and qualitative angiographic degrees of collateral flow has been demonstrated to be quite large, 20 quantitative indices of collateral circulation may be better markers of the functional significance of collateral vessels, in particular in recruitable (Rentrop-grade 1) collaterals. 14,21,22 A recent study, 23 nonetheless, reported High blood pressure reduces collaterals J Koerselman et al good correlation between a novel angiographic method of assessment and function. This is to be expected considering the fundamental physical law describing that vessel radius is related to the fourth power of flow.…”
Section: Discussionmentioning
confidence: 99%
“…The ipsilateral contribution to collateral flow has been reported to range from 17% (our study) to 53%. 9 Presence of collaterals prevented chest pains and ST-segment changes during PTCA compared with patients without collaterals, as spontaneously visible collaterals are more effective than recruitable collaterals. In humans, the effect of nitroglycerin on collateral function has mainly been assessed by means of scintigrams.…”
Section: Discussionmentioning
confidence: 89%
“…Meier et al 9 found spontaneously visible collaterals to be four times as frequent as recruitable collaterals when they considered collateral filling ≥ grade 2 (Rentrop classification). In contrast, Piek et al 10 found recruitable collaterals to be four times as frequent as spontaneously visible collaterals when using the same criteria of collateralization.…”
Section: Discussionmentioning
confidence: 99%